2015
DOI: 10.1002/jor.23038
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and structure–function relationships in articular cartilage repaired using IGF‐I gene‐enhanced chondrocytes

Abstract: Several studies have demonstrated the benefits of IGF-I gene therapy in enhancing the histologic and biochemical content of cartilage repaired by chondrocyte transplantation. However, there is little to no data on the mechanical performance of IGF-I augmented cartilage grafts. This study evaluated the compressive properties of full-thickness chondral defects in the equine femur repaired with and without IGF-I gene therapy. Animals were randomly assigned to one of three study cohorts based on chondrocyte treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Many studies have shown a strong correlation between the sGAG content and the compressive properties of native cartilage, but the influence of sGAG on the compressive properties of tissue engineered cartilage is less understood . A few previous studies have identified a correlation between the sGAG content and the aggregate modulus of tissue engineered cartilage . This study also revealed a correlation between the sGAG content and the aggregate modulus ( R 2 = 0.67, p = 0.046, Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Many studies have shown a strong correlation between the sGAG content and the compressive properties of native cartilage, but the influence of sGAG on the compressive properties of tissue engineered cartilage is less understood . A few previous studies have identified a correlation between the sGAG content and the aggregate modulus of tissue engineered cartilage . This study also revealed a correlation between the sGAG content and the aggregate modulus ( R 2 = 0.67, p = 0.046, Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, these apparent composition–function relationships were not maintained for enzymatically degraded cartilage explants, whose mechanical response to altered osmotic environments did not conform to the native tissue response, particularly the response of meniscus tissues with similar sGAG concentrations. While some studies have explored the particular effects of aging, degeneration, and repair in the structure–function relationships of a given tissue type (typically cartilage) and even suggested the interaction between sGAG and collagen in the compressive properties of cartilage, our study uncovered inter‐tissue relationships that, to our knowledge, have not been previously described. Furthermore, the trends reported here seem to hold for other musculoskeletal soft tissues outside the realm of the sGAG concentration spectrum tested, such as tendon (with collagen/dry mass values in the order of 100 µg/mg and sGAG/dry mass of approximately 1 µg/mg for flexor bovine tendons in 6‐month‐old calves) …”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, sc-AAV produces higher levels of protein more quickly and, for this reason, it could become the preferred choice for gene therapy trials [60]. rAAV is used for the delivery of IGF-1 [61][62][63], TGF-β [2,64], FGF-2 [65], SOXs [59,64,66] and IL1ra genes [67]. scAVV is used for the delivery of IL1ra [68] (Table 1).…”
Section: Viral Vectormentioning
confidence: 99%
“…7). The cell vehicles, with and without scaffolds, are MSCs of different origin [14, 17, 26, 27, 40-42, 46, 54, 55, 59, 61, 71-75, 77, 82], chondrocytes [16,21,44,59,61,62,70,83] and, to a lesser extent, fibroblasts [18,56]. In fewer cases vectors are implanted into scaffolds without cells as vehicles: the plasmid vector is supported by a collagen I sponge or complexed with bPEI-HA via a porous oligo[poly(ethylene glycol) fumarate] hydrogel scaffold [22,24] and adenoviral vector by DCBM [51] (Table 1).…”
Section: Indirect Proceduresmentioning
confidence: 99%